#emergencymedicine: A TikTok Content Analysis of Emergency Medicine-related Content - Madison Stolly; Erika Wilt; Nathan Gembreska; Mohamad Nawras; Emily Moore; Kelly Walker; Rhonda Hercher; Mohamad Moussa (Western Journal of Emergency Medicine)
Background: TikTok has rapidly become one of the most extensively downloaded and used social media platforms worldwide. Our focus on emergency medicine (EM)-related content on TikTok is to identify what specific video characteristics result in higher degrees of audience engagement, defined in this study as a total of video likes, comments, and shares. Methods: Five second-year medical students using newly created TikTok accounts independently downloaded the first 100 videos to appear using the hashtag #emergencymedicine. The videos were reviewed for 52 variables. We performed a multiple linear regression analysis to examine the relationship between the variables and video engagement. Results: Of the examined videos, 45.8% (222/484) were produced by physicians (MD or DO). Approximately half, 50.0% (242/484), had an educational component, while 55.4% (268/484) of videos were judged to have an entertainment component. Preliminary findings indicate that among TikTok videos featuring #emergencymedicine, a statistically significant positive correlation exists between video engagement and the presence of a healthcare identifier, (ie, individuals wearing white coats or scrubs). No significant correlation was observed between video engagement and video creators’ self-identification as a healthcare professional, use of entertainment, or use of education. A notable negative correlation was identified between video engagement and the inclusion of music. Conclusion: We identified qualities associated with negative and positive correlation with video engagement. For the 100 videos, only healthcare attire, such as wearing a white coat or scrubs, showed a significant positive correlation with engagement, while those with background music showed a negative correlation. Our study offers insight into how EM professionals can effectively use characteristics associated with higher engagement rates to relay information to a wider audience on TikTok.